Why are spreading deceptive political conspiracy theories ethically wrong? - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
Conspiracy theories in expert circles generally have a bad reputation, which is conditioned by the fact that according to some studies, the spread of conspiracy theories has a number of negative consequences: it increases society’s indifference to politics, distrust of science etc. However, there are some other researchers who believe that the spread of conspiracy theories has positive effects: it increases the accountability of authorities, contributes to the disclosure of hidden conspiracies, and, in general, is an indicator of the transparency of society. Therefore, attempts by state institutions to prevent the spread of such theories can lead to even more negative consequences. This article analyzes these two approaches to the problem and argues that the dissemination of conspiracy theories is ethically wrong mainly in cases when we are dealing with deceptive political conspiracy theories. These are deceptive, misleading theories that certain political groups use to serve their political agenda. From an ethical point of view, the wrongness of spreading deceptive political conspiracy theories is based on the fact that as a kind of fake news, they mislead and harm society, are mainly used by populist and authoritarian politicians to polarize various social groups, justify their illegitimate actions, and reject the principle of equality among members of society.